A Primer of Neuroimmunological Disease - Pachner, Andrew R. (Springer New York : Imprint: Springer, 2012)
A Primer of Neuroimmunological Disease is a significant new resource for anyone interested in conditions such as multiple sclerosis(MS), myasthenia gravis, and neurological infections.  It is a practical and balanced guide to the diagnosis and treatment of neuroimmunological disease. A Primer of Neuroimmunological Disease distinguishes itself by providing a range of features not generally included in texts on neuroimmunology. These include broad presentation of information in the form of figures and tables; strong cohesion among topics by focusing on a few prototypic neuroimmunological diseases, which serve as a foundation from which to explore other neuroimmunological diseases; a single author perspective, with references across chapters; and a focus on the overlap between neuroimmunological and neuroinfectious diseases.  Neurologists, immunologists, infectious disease specialists, neuroscientists and others interested in neuroimmunological diseases such as MS will find A Primer of Neuroimmunological to be a state-of-the-art resource.